Peran Pemuda Islam Dalam Pengelolaan Sampah Rumah Tangga di Kecamatan Sunggal Kabupaten Deli Serdang - Rangkuti, Bachtiar Ahmad Fani; Aulia, Rahma; Yusdha, Nur Aflah; Harefa, Hajriani (Prodi Tata Negara (Siyasah) IAIN Langsa, 2023)
The production of waste every day is increasing in line with the increasing population and consumption patterns of the people. The thing that must be done to overcome the increase in the volume of waste is to reduce the volume of waste. So that in this study is to describe the role of youth in household waste management in Sunggal District, Deli Serdang Regency, how the general impact and the positive impact of the waste management. This research uses a descriptive method. Which was carried out at Jalan Mesjid Pasar IV Tanjung Gusta, Sunggal District, Deli Serdang Regency by conducting interviews and observations to obtain data needed by researchers in seeking information related to the impact of waste management in the community in the area. The results of this study indicate that the waste management site that was built and developed by the youth brings together local people who work to manage the waste. This waste management has also been developed into a start-up company where the results of waste management are developed into decorative items or items that can be reused based on selling value. With the construction and development of this waste management site, it certainly has a positive impact on the local community which creates jobs that can help improve the economy of the surrounding community